Bioactivation Routes of Gelatin-Based Scaffolds to Enhance at Nanoscale Level Bone Tissue Regeneration - Raucci, Maria Grazia; D'Amora, Ugo; Ronca, Alfredo; Demitri, Christian; Ambrosio, Luigi (Frontiers in Bioengineering and Biotechnology, 2019)
The present work is focused on the development of gelatin-based scaffolds crosslinked through carbodiimide reaction and their bioactivation by two different methods: (i) surface modification by inorganic signals represented by hydroxyapatite nanoparticles precipitated on scaffold through biomimetic treatment; (ii) analogue of BMP-2 peptide decoration. The results showed the effects of polymer concentration and crosslinking time on the physico-chemical, morphological and mechanical properties of scaffolds. Furthermore, a comparative study of biological response for both bioactivated structures allowed to evaluate the influence of inorganic and organic cues on cellular behaviour in terms of adhesion, proliferation and early osteogenic marker expression. The bioactivation by inorganic cues induced positive cellular response compared to neat scaffolds in terms of increased cell proliferation and early osteogenic differentiation of human mesenchymal stem cell (hMSC), as evidenced by the Alkaline phosphatase (ALP) expression. Similarly BMP-2 peptide decorated scaffolds showed higher values of ALP than biomineralized ones at longer time. The overall results demonstrated that the presence of bioactive signals (either inorganic or organic) at nanoscale level allowed an osteoinductive effect on hMSC in a basal medium, making the modified gelatin scaffolds a promising candidate for bone tissue regeneration.